Redescription and phylogenetic position of the early Miocene penguin Paraptenodytes antarcticus from Patagonia - Bertelli, Sara, Ph. D.; Giannini, Norberto P.; Ksepka, Daniel T. (New York, NY : American Museum of Natural History, 2006)
36 p. : ill. 26 cm. Includes bibliographical references (p. 27-28). Paraptenodytes antarcticus is one of the best-known and most complete fossil penguins. This taxon is so distinctive that it has traditionally been classified in its own subfamily (Sphenisciformes: Paraptenodytinae) separate from all living penguins (Spheniscinae). The well-preserved partial skull of P. antarcticus is one of our richest sources of data on early penguin cranial morphology. We provide an updated description of the skull of P. antarcticus in a comparative context and use this information to explore the phylogenetic relationships of this taxon. Three cladistic analyses using an osteology dataset, a larger morphological dataset (including osteological, soft tissue, behavior, and oological characters) and a combined (morphological + molecular) dataset all recover Paraptenodytes as the sister taxon to a clade including all extant penguins. The placement of Paraptenodytes outside the crown clade of extant penguins reveals the order in which many spheniscid synapomorphies were acquired and lends support to the hypothesis that modern penguins had Subantarctic ancestors.